Sodium phosphate loading - Stern, R.
This month's Performance Tips looks at the subject of Sodium Phosphate loading. About a year ago, an article in the Performance Matters section of Cycling Weekly suggested that sodium phosphate loading could increase time trial performance. The article said that 25 mile time could be reduced by about 8 % with phosphate, which, is a hefty increase in performance. In contrast the hormone erythropoietin (EPO) can boost performance around 10 %. Introduction As a sport scientist, I decided to investigate the effects of sodium phosphate loading for my thesis. However, I decided to examine the effects of phosphate loading on a 10 mile performance trial on the Kingcycle ergometer, as this had not been previously researched. Background Whilst reviewing the literature it became apparent that very little research had been carried out on phosphate loading, and a lot less on the various phosphates and performance. There were approximately only ten previous studies on phosphate and performance, and results from these were equivocal. Several studies had shown an improvement in VO2 max of around 10 %, whilst others showed no improvements. Previous in vitro and in vivo research suggested that phosphate loading altered blood biochemistry and increased the concentration of haematological parameters such as 2,3-Diphosphoglycerate (2,3-DPG) and intracellular inorganic phosphorous (Pi). The delivery of oxygen to the tissues is characterised by the oxygen - haemoglobin (O2) dissociation curve. This curve has a vague 's' shape and can be altered under various conditions. For instance, the curve can be right shifted with increases in i) temperature, ii) CO2, iii) lactic acid and iv) 2,3-DPG. If the O2 curve is right shifted, there is a greater unloading of oxygen at the venous end of the capillaries, allowing the muscles to utilise more oxygen. Other recent research has suggested that phosphate loading increases both cardiac output and VO2 during exercise which would suggest that oxygen unloading is decreased. However, this study showed the largest improvements in performance and therefore, the exact mechanisms for phosphate working are not yet known. Several studies have shown no improvement in performance, whilst other studies have shown an increase in VO2 max of around 10 %. Only one previous study has actually shown an improvement in time trial ability. This study consisted of cyclists riding a 40 km trial in the laboratory after previously consuming either the placebo or phosphate in a double blind manner for five days. Subjects in the study improved their 40 km time by 3.5 minutes, increased their VO2 max 10 % and increased their power output by 17 %. Phosphate has also been examined in anaerobic tests (30 second Wingate sprint) and whilst the phosphate elevated the cyclists' blood phosphate levels it had no effect on Wingate performance or repeated Wingate trials. However, the phosphate used in this trial was dibasic sodium phosphate and this is known to alter the ratio of dibasic and monobasic phosphate (plasma phosphate). Whilst dibasic phosphate may increase the removal of lactic acid, the consequence of lowering the dibasic / monobasic ratio may directly contribute to fatigue at the actomyosin ATPase level, which suggests that dibasic sodium phosphate is not ergogenic. Studies that have shown no improvement in any performance measure, have still been shown to alter physiological parameters, such as altering blood biochemistry and decreasing cardiac output (amount of blood pumped out of the heart) at a given workload and therefore, might still be ergogenic. Present Study The present study used six well trained cyclists (all subjects had beaten 23 minutes for a 10) and the average personal best was 22mins 24secs. Average VO2 max was 4.52 l·min-1, whilst average maximum aerobic power was 444 W measured on a Kingcycle ergometer. Subjects took the placebo or phosphate (1g four times a day) for six days. The subjects carried out a control, placebo and phosphate trial. The control trial averaged 21min51sec (322 W), the placebo trial was 21min58 sec (317 W) and the phosphate trial was completed in an average of 21min14sec (344 W). As can be seen subjects improved around 40 seconds, which is a large improvement and represents around an 8 % increase in power. One subject, however, went backwards when using the phosphate, which means that the average improvement was actually greater than 40 seconds. During the trials, subject's heart rates, lactate and their perceptions of effort were not altered. Therefore, phosphate loading increased performance whilst eliciting similar metabolic demands. This could suggest that VO2 max was increased with phosphate loading and supports other recent studies. Conclusion It is possible that phosphate loading might have differing effects on events that require different exercise intensities (e.g. 10's, 25's, and 50's), although research has not actually tested this theory. In the near future, I hope to be investigating the effects of phosphate loading on differing aspects of exercise and performance and in subjects of different abilities (fit, trained, elite, men, women, young and old). In conclusion, current research suggests that phosphate loading increases performance in men in maximal and endurance exercise and has been shown to increase performance in 10's, 25's and max tests. A possible side effect of phosphate loading is that of gastrointestinal distress, which resulted in one subject vomiting after taking the phosphate. However, the exact mechanisms that cause these improvements have yet to be fully elucidated.